INTERFERENSI LEKSIKAL, FRASIOLOGIS, DAN KLAUSAL BAHASA JAWA KE DALAM BAHASA INDONESIA DALAM MAJALAH AULA - Muntiqoh Muntiqoh (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The purpose of this study to describe about (1) lexical interference Java language into Indonesia, (2) phrase interfence Java language into Indonesia, (3) clause interference Java language into Indonesia in Aula magazine. This study take the data from Aula magazine because it’s a magazine for Nahdlatul Ulama (NU) society, 2011-2012. The kind of this research is analysis text. The data that found then analyze using descriptive quantitative method.The data analysisin this research use interactive analysis method/form. And continue until finish, so the data bored. The data selectede, next clasified based on lexical, phrase, and clause interference.The result of this research got the description such as: (1) there is lexical interference Java language into Indonesia very much, (2) ) there is phrase interference Java language into Indonesia, (3) ) there is clause interference Java language into Indonesia in Aula magazine. Thus, the interference occur in lexical, phrase and clause.